Effect of composite surface treatment and aging on the bond strength between a core build-up composite and a luting agent - Cotes, Caroline [UNESP]; Cardoso, Mayra; Melo, Renata Marques de [UNESP]; Valandro, Luiz Felipe [UNESP]; Bottino, Marco Antonio [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2015)
Objective: The purpose of this study was to assess the influence of conditioning methods and thermocycling on the bond strength between composite core and resin cement. Material and Methods: Eighty blocks (8x8x4 mm) were prepared with core build-up composite. The cementation surface was roughened with 120-grit carbide paper and the blocks were thermocycled (5,000 cycles, between 5 degrees C and 55 degrees C, with a 30 s dwell time in each bath). A layer of temporary luting agent was applied. After 24 h, the layer was removed, and the blocks were divided into five groups, according to surface treatment: (NT) No treatment (control); (SP) Grinding with 120-grit carbide paper; (AC) Etching with 37% phosphoric acid; (SC) Sandblasting with 30 mm SiO2 particles, silane application; (AO) Sandblasting with 50 mu m Al2O3 particles, silane application. Two composite blocks were cemented to each other (n=8) and sectioned into sticks. Half of the specimens from each block were immediately tested for microtensile bond strength (mu TBS), while the other half was subjected to storage for 6 months, thermocycling (12,000 cycles, between 5 degrees C and 55 degrees C, with a dwell time of 30 s in each bath) and mu TBS test in a mechanical testing machine. Bond strength data were analyzed by repeated measures two-way ANOVA and Tukey test (alpha=0.05). Results: The mu TBS was significantly affected by surface treatment (p=0.007) and thermocycling (p=0.000). Before aging, the SP group presented higher bond strength when compared to NT and AC groups, whereas all the other groups were statistically similar. After aging, all the groups were statistically similar. SP submitted to thermocycling showed lower bond strength than SP without thermocycling. Conclusion: Core composites should be roughened with a diamond bur before the luting process. Thermocycling tends to reduce the bond strength between composite and resin cement.
Keywords: Composite resins; Aging; Cementation